Viabilility of Rams Epididymal Sperm after Preservation in Low Temperature (5oc) - Rizal, M; Herdis, Herdis; Boediono, A (ANIMAL PRODUCTION, 2004)
The purpose of this research was to evaluate the viability of ram epididymal sperm collected from fresh caudal epididymis (H-0) or after storage in low temperature (5oC, in refrigerator) for one (H-1), two (H-2), and three (H-3) days.  Collected sperm were diluted in modified Tris extender and they were preserved in refrigerator up to four days.  The viability of diluted sperm was evaluated daily base on motility and sperm live.  Results indicated that mean sperm concentration after sperm diluted with 0.05 ml Tris extender of caudal epididymis was 2745 million/ml. Sperm motility and percentage of live for H-0 (71.25% and 82.83%) and H-1 (70.00% and 79.17%) were significantly higher (P<0.05) than H-2 (61.25% and 69.83%) and H-3 (51.67% and 66.17%).  Percentages of sperm motility and live of diluted sperm and preserved in refrigerator for H-0 were significantly higher (P<0.05) than H-1, H-2, and H-3.  These results showed that epididymal sperm collected from caudal epididymis up to three days of preservation (without further storage of the diluted sperm) could be used for artificial insemination or in vitro fertilization programs.  Diluted sperm of H-0 and H-1 could be preserved in refrigerator for two days and H-2 for one day. (Animal Production 6(1): 30-36 (2004) Key Words: Epididymal Sperm, Viability, Rams